Self-Reported Empathy among Nursing and Medical Students at the University of Ibadan, Oyo State: A Cross-Sectional Study - Lucia OJEWALE (The Nursing Scope, 2026)
Background: Empathy is a fundamental professional competency that enables healthcare professionals to understand patients' perspectives, emotions, and experiences, thereby enhancing patient-centred care. Higher levels of empathy have been associated with improved clinical outcomes, patient satisfaction, and psychological well-being. However, evidence on empathy among Nigerian nursing and medical students remains limited. Aim: To assess and compare self-reported empathy among nursing and medical students at the University of Ibadan, Nigeria, by programme, level of study, and gender. Method: A descriptive cross-sectional study was conducted among 253 nursing and medical students who had commenced clinical placements. Participants were selected using proportionate stratified random sampling. Data were collected using the Jefferson Scale of Empathy–Health Professional Students Version (JSE-HPS) and analysed using IBM SPSS Statistics Version 20. Descriptive statistics, Mann–Whitney U, and Kruskal–Wallis tests were used, with statistical significance set at p < .05. Findings: Most participants were medical students (77.5%), aged 22–24 years (48.4%), and female (53.9%). The overall mean empathy score was 106.9 (SD = 14.5). Self-reported empathy did not differ significantly by programme or gender but varied significantly by level of study, with students in higher academic levels reporting higher empathy scores. Conclusion: Self-reported empathy was comparable between nursing and medical students and between male and female students. Although empathy differed by level of study, the cross-sectional design limits conclusions about changes over time. Recommendation: Educational institutions should deliberately integrate empathy-enhancing strategies, including reflective practice, communication skills training, simulation-based learning, mentorship, and patient-centred clinical experiences, into nursing and medical curricula, with periodic assessment of students’ empathy to support its continued development throughout training. Keywords: Empathy; Nursing students; Medical students; Healthcare professional students; Clinical education.